2021
DOI: 10.5194/adgeo-56-1-2021
|View full text |Cite
|
Sign up to set email alerts
|

Modeling public charging infrastructure considering points of interest and parking potentials

Abstract: Abstract. Considering climate change, it is essential to reduce CO2 emissions. The provision of charging infrastructure in public spaces for electromobility – along with the substitution of conventional power generation by renewable energies – can contribute to the energy transition in the transport sector. Scenarios for the spatial distribution of this charging infrastructure can help to exemplify the need for charging points and their impact, for example on power grids. We model two kinds of demand for publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Little literature meticulously analysed the impact of realistic factors such as POI (Point of Interest) and intersection impedance on traffic flow in the road network. In recent years, more and more studies notice static traffic impact factors such as schools, shopping malls, and parks (i.e., POIs), which can be summarized into three categories: identification of urban functional areas [25][26][27][28], analysis of the spatial distribution of a specific type of public facilities [29][30][31], and analysis of urban traffic characteristics based on POI data [22,25,32,33]. It is concluded that the impact of static traffic factors on cities is not negligible, and they have significant value for research on sustainable urban development.…”
Section: Introductionmentioning
confidence: 99%
“…Little literature meticulously analysed the impact of realistic factors such as POI (Point of Interest) and intersection impedance on traffic flow in the road network. In recent years, more and more studies notice static traffic impact factors such as schools, shopping malls, and parks (i.e., POIs), which can be summarized into three categories: identification of urban functional areas [25][26][27][28], analysis of the spatial distribution of a specific type of public facilities [29][30][31], and analysis of urban traffic characteristics based on POI data [22,25,32,33]. It is concluded that the impact of static traffic factors on cities is not negligible, and they have significant value for research on sustainable urban development.…”
Section: Introductionmentioning
confidence: 99%